Implementation of Qur'an-Based Women's Empowerment Program 5.0 in Strengthening Religious Literacy - Sri Tuti Rahmawati; Esi Hairani; Yanti Susanti; Chalimatus Sa'dijah; Nadjematul Faizah (Civiliza Publishing, 2026)
This study aims to analyze the implementation of a women empowerment program based on Al-Qur’an 5.0 in strengthening religious literacy at Institut Attarkiyah Islamiah, Narathiwat, Thailand. This community service program was conducted to address the gap between normative religious understanding and its contextual application in a multicultural educational environment. The method used was a participatory approach through workshops, interactive discussions, demonstrations, and guided practice. The results indicate that the program was effective in improving participants’ understanding of Qur’anic values, teaching skills, and active participation in learning. Participants also showed increased confidence in applying Qur’anic teachings in daily life. The integration of digital-based learning and contextual approaches contributed significantly to the effectiveness of the program. This study concludes that the implementation of Al-Qur’an 5.0-based empowerment programs can enhance religious literacy and strengthen the role of women as agents of social and spiritual transformation.